Frequency of glucocorticoid resistance and dependency in Crohn's disease. Issue 3 (March 1994) - Munkholm, P; Langholz, E; Davidsen, M; Binder, V
Abstract : The outcome of the first steroid treatment course was prospectively studied in a regional cohort of 196 patients with Crohn's disease diagnosed 1979-1987. The immediate outcome after 30 days, and the prolonged outcome 30 days after treatment had stopped, are described. In all 109 patients treatment was analysed. Complete remission was obtained in 48%, partial remission in 32%, and no response in 20% within 30 days of treatment. Among primary responders (complete and partial remission), 55% remained in prolonged response after treatment had finished, while 45% relapsed or could not be withdrawn from treatment within one year. Localisation of disease, age, sex or clinical symptoms did not significantly correlate with outcome, which can be summarised as prolonged steroid response in 44%, steroid dependency in 36%, and steroid resistant in 20% of the patients.